Rivaroxaban for thromboprophylaxis after orthopaedic surgery: Pooled analysis of two studies - Fisher, William D.; Eriksson, Bengt I.; Bauer, Kenneth A.; Borris, Lars; Dahl, Ola E.; Gent, Michael; Haas, Sylvia; Homering, Martin; Huisman, Menno V.; Kakkar, Ajay K.; Kälebo, Peter; Kwong, Louis M.; Misselwitz, Frank; Turpie, Alexander G. G. (Thrombosis and Haemostasis, 2007)
Rivaroxaban (BAY 59-7939) is an oral, direct factor Xa inhibitor in clinical development for the prevention and treatment of venous thromboembolism (VTE). This analysis of pooled results from two phase II studies of rivaroxaban for VTE prevention after major orthopaedic surgery aimed to strengthen the conclusions of the individual studies. One study was conducted in patients undergoing total hip replacement (THR; N=722), and one in patients undergoing total knee replacement (TKR; N=621). In both studies, patients were randomized, doubleblind, to oral, twice-daily (bid) rivaroxaban beginning after surgery, or subcutaneous enoxaparin (40 mg once daily beginning before THR, and 30 mg bid beginning after TKR). Treatment continued until mandatory bilateral venography was performed 5–9 days after surgery. Total VTE (deep vein thrombosis, pulmonary embolism, and all-cause mortality) occurred in 16.1–24.4% of per-protocol patients receiving rivaroxaban 5–60 mg, and 27.8% receiving enoxaparin (n=914). There was a flat dose response relationship between rivaroxaban and total VTE (p=0.39). Major bleeding (safety population, n=1,317) increased dose-dependently with rivaroxaban (p<0.001), occurring in 0.9%, 1.3%, 2.1%, 3.9%, and 7.0% of patients receiving rivaroxaban total daily doses of 5, 10, 20, 40, and 60 mg, respectively, versus 1.7% of patients receiving enoxaparin. No routine coagulation monitoring was performed, and there were no significant differences between dose response relationships with rivaroxaban after THR and TKR. Overall, rivaroxaban total daily doses of 5–20 mg had the most favorable balance of efficacy and safety, relative to enoxaparin, for the prevention of VTE after major orthopaedic surgery.
Keywords: Rivaroxaban; venous thromboembolism; orthopaedic surgery; total hip replacement; total knee replacement